DNA damages and premature aging - Temviriyanukul, Piya (Thai Journal of Toxicology, 2020)
Deoxyribonucleic acid (DNA) is a genetic material of all organisms, which is essential for usual living. Therefore, there are cellular DNA repair pathways to protect genetic material from DNA damages, and promote genome stability. If there is a defect in the DNA repair processes, genetic material is not protected leading to genome instability. The consequences of genome instability ranges from cell dysfunction to pathological diseases, such as premature aging. An accumulation of damaged DNA, which is mainly due to free radical attack, is one of the important factors contributing to the premature aging. The investigation on the relationship between DNA damages and premature aging may lead to the behavioral change of people in order to avoid DNA damaging agents, the generation of chemicals, which preclude premature aging or promote healthy aging by enhancing functions of the DNA repair pathways.